Forecasting of Wind Speed Using an Interval-Based Least Square Method - Aslam, Muhammad; Albassam, Mohammed (Frontiers in Energy Research, 2022)
A new least square method (LSM) under indeterminacy is proposed in this manuscript. The proposed LSM under indeterminacy is known as the neutrosophic least square method (NLSM). The NLSM is proposed to forecast the wind speed when the data is in the interval. The trended line under indeterminacy is introduced and applied using wind speed data. The time series plots under neutrosophic statistics are given. The comparative study shows that the proposed NLSM is more efficient and informative to apply for the forecasting of wind speed.